(untitled) (The Pretoria Student Law Review, 2021)
India’s Competition Act, 2002, deals with anti-competitive agreements in section 3, dividing them into horizontal and vertical agreements. Horizontal agreements are those between enterprises at the same stage of the production chain, such as between two rivals; these are dealt with under a presumptive rule that appreciable adverse effect on competition is presumed. Vertical agreements are those between enterprises at different stages of the production chain, such as between manufacturer and distributor. These are dealt with on a rule of reason basis, ie appreciable adverse effect on competition needs to be proved by the Competition Commission of India, which essentially means that the positive as well as negative impact of such agreement on competition will have to be taken into account before coming to any conclusion. These concepts will be discussed at length in the later sections of this article. The focus of this article is on vertical agreements and the resultant market distortions. The following segments of the paper will deal with the legislative history of the infant competition law in India, and will analyse the impressions of the vertical restraints in the Indian competition fabric with reference to the Competition Act, 2002 (yet to be enforced), Monopolies and Restrictive Trade Practices Act, 1969 (MRTP), and the Indian and international case laws. The article also touches on the issues of enforcement and the treating of the consequential developmental disorders in the economy.